The Enigma of Basilar Artery Dissections Secondary to Vasospasm Following Subarachnoid Hemorrhage. Exploration of the Unknown Effect of Superior Cervical Ganglia: A Preliminary Experimental Study - Zeynal, Mete; Sahin, Mehmet Hakan; Kanat, Ayhan; Karadag, Mehmet Kursat; Sipal, Sare; Ergene, Saban; Aydin, Mehmet Dumlu (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2024)
Background Life-threatening basilar artery dissection (BAD) can be seen following subarachnoid hemorrhage (SAH), but it is not clear whether SAH causes dissection, or not. This study aims to investigate the relationship between degenerative changes in the superior cervical ganglia and the dissection rate of the basilar artery.Method In this study, after 3 weeks of experimental SAH, animals were decapitated. Eighteen rabbits were divided into three groups according to their vasospasm indices. The basilar arteries were examined by anatomical and histopathologic methods.Results Basilar dissection with high vasospasm index (VSI) value (VSI > 3) was detected in six animals (group I); severe basilar edema and moderate VSI value (>2.4) were detected in seven rabbits (group II); and slight VSI value (<1.5) was detected in five subjects (group III). The degenerated neuron densities of the superior cervical ganglia were 12 ± 4 n/mm3 in group I, 41 ± 8 n/mm3 in group II, and 276 ± 78 n/mm3 in group III. The dissected surface values/lumen values were calculated as (42 ± 1)/(64 ± 11) in G-I, (21 ± 6)/(89 ± 17) in group II, and (3 ± 1)/(102 ± 24) in group III. If we look at these ratios as a percentage, it was 62% in group I, 23% in group II, and 5% in group III.Conclusion Inverse relationship between the degenerated neuron densities of the superior cervical ganglia and the dissected surface values of the basilar artery was observed. Common knowledge is that BAD may lead to SAH; however, this study indicates that SAH is the cause of BAD.
Keywords: basilar artery vasospasm; dissections; subarachnoid hemorrhage; superior cervical ganglia